Національний характер мовної особистості в контексті міжкультурної комунікації - Котов, М.В.; Солощук, Л.В. (Логос, 2010)
The article deals with the problem of national character inherent in a language identity within the framework of cross-cultural communication. Special attention is paid to the phenomenon of the national character and the problems connected with its determination and investigation as well as to the extent of influence on communicative processes within the framework of cross-cultural dialogue.
ORCID ID: http://orcid.org/0000-0001-8327-5197
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; cross-cultural communication, language identity, national character, verbal and non-verbal communicative components